Religious Fundamentalism: Constructs and Measurement for Indonesian Muslims - Yuminah, Yuminah; Zulkifli, Zulkifli; Fahri, Muhamad; Latifa, Rena; Nuraeni, Neng Sri (Psikis : Jurnal Psikologi Islami, 2025)
Religious fundamentalism constitutes an attitudinal and behavioral approach to religious adherence underpinned by an intratextual cognitive framework, which prioritizes the literal interpretation and comprehension of sacred texts. This principle-oriented cognitive paradigm is not contingent upon meaning but rather on process, where in the text itself dictates the methodology of its own reading and interpretation. Consequently, this approach negates dialogical engagement, reducing the dichotomy to either adherence to textual truth or its rejection, thereby fostering epistemic closure to alternative sources of truth construction. While prior studies have sought to quantify religious fundamentalism in Indonesia through diverse constructs and instruments, none have explicitly centered on the intratextual cognitive dimension, raising critical questions regarding the development of a robust measurement framework grounded in this paradigm. Employing confirmatory factor analysis (CFA) and Rasch model analysis with a sample of 323 respondents, this study addresses this gap. The CFA results demonstrated that the proposed construct of religious fundamentalism, comprising six dimensions (divine, inerrant, authoritative, self-interpretive, privileged, and unchanging) and operationalized through 12 items, yielded a model with satisfactory fit indices, wherein 9 items exhibited validity and 3 were invalid. Concurrently, Rasch model analysis confirms that all items conform to the model’s expectations, effectively measuring intratextual paradigm-based fundamentalism. Notably, certain items exhibited high difficulty indices, attributable to respondent ambivalence when engaging with contentious statements. These findings present a validated instrument for evaluating religious fundamentalism through an intratextual approach, specifically adapted to the socioreligious framework of Indonesian Muslim communities. Consequently, this tool is capable of capturing the manifestations of religious fundamentalism in Indonesia with an empirical foundation, thereby enabling a more precise understanding and analysis of religious dynamics within Indonesian society